A metal–organic gel based on Fe(iii) and bi-pyridine ligand for template synthesis of core/shell composite polymer nanowires. Issue 43 (17th October 2018) - Li, Botian; Xiao, Da; Deng, Dongsheng; Ye, Haimu; Zhou, Qiong; Tang, Liming
Abstract : In this study, the self-supporting composite polymer nanowires were synthesized using a thermal-stable Fe(iii ) metal–organic gel as template. Abstract : In this study, a novel self-assembled metal–organic gel was synthesized from ferric nitrate and a di-topic ligand, bis(3-pyridyl)terephthalate. The gel consisted of a three dimensional network of uniform nanofibers. The gelation exhibited high selectivity to Fe(iii ) based on metal–ligand coordination. The molar ratio of Fe 3+ to ligand had a large influence on the assembly process and the morphology of the gel. The metallogel displayed multi-stimuli responsiveness and excellent heat resistance, thus was further applied as a thermo-stable template for the polymerization of N, N ′-methylene bisacrylamide to produce the core/shell polymer composite nanowires. Subsequently, the polymer nanotubes were obtained after ammonia post-treatment, comfirming the feasibility of the template synthesis strategy. According to the rheological measurements, the gel-like products of the composite nanowires exhibited better mechanical strength compared to the gel template.